Human Resource Competence Effect on the Quality of Regional Work Unit of Financial Reports with the Government's Internal Control System - Helmy, Arif; Silviana, Silviana (Newinera Publisher, 2024)
The purpose of this study is to examine the influence of human resource competence on the quality of financial reports of Local Government Work Units (SKPD), with the government internal control system as a moderating variable. This research adopts an explanatory approach utilizing quantitative methods. The population consists of 38 SKPD holding general functional positions responsible for financial reporting in the West Java Provincial Government. The sampling method employed is census, encompassing the entire population as the research sample. Data collection involves primary data gathered through questionnaires. Hypothesis testing utilizes Moderation Regression Model with the assistance of Statistical Product and Service Solution (SPSS) version 25. The findings of this study demonstrate that human resource competence has a positive and significant influence on the quality of SKPD financial reports. However, the government's internal control system does not enhance the influence of human resource competence on the quality of SKPD financial reports. Recommendations stemming from this research include urging the West Java Provincial Government to enhance human resource competence, particularly in accounting cycle skills and regulatory knowledge. Additionally, it is advised to strengthen the Internal Control System (SPIP) with a focus on effective communication of risk management, regular briefing sessions, workload analysis, implementation of measurable rewards and punishments, clear Standard Operating Procedures (SOP), and structured internal control monitoring.